Mitigating N2O emissions from soil: From patching leaks to transformative action - Decock, C.; Lee, Juhwan; Pereira, E.; Necpalova, M.; Tendall, D.; Six, J. (2015)
Further progress in understanding and mitigating N2O emissions from soil lies within transdisciplinary research that reaches across spatial scales and takes an ambitious look into the future.